VD_FINDINFO ACH 218/17 - 90/2018 vom 14. Mai 2018 - VD Tribunal cantonal (2018)
APTITUDE AU PLACEMENT, DISPONIBILITÉ AU PLACEMENT, ÉTUDIANT, DURÉE, AC | 15 LACI, 59 LACI, 60 al. 4 LACI, 8 al. 1 let. f LACI